Social expenditure cyclicality - Jalles, João Tovar (2022)
This paper provides a novel dataset of time-varying measures of cyclicality in social spending for an unbalanced panel of forty-five developing economies from 1982 to 2012. We focus on four categories of government social expenditure: health, social protection, pensions, and education. We find that in developing countries social spending has been acyclical over time, with the exception of spending on pensions. However, sample averages hide marked heterogeneity across countries, with many individually showing procyclical behavior in different social spending categories. The use of time-varying measures of social spending cyclicality overcomes the major limitation of previous studies in assessing the drivers of fiscal cyclicality that rely solely on cross-country regressions and, therefore, cannot account for country-specific as well as global factors. Using weighted least squares regressions, we find that the degree of social spending (pro)cyclicality is negatively associated with financial deepening, the level of economic development, trade openness, government size, and political constraints on the executive.